One-pot tandem cyclization of enantiopure asymmetric cis-2,5-disubstituted pyrrolidines: Facile access to chiral 10-heteroazatriquinanes - Wang, Ping-An; Zhang, Sheng-Yong; Kagan, Henri B. (Beilstein Journal of Organic Chemistry, 2013)
A series of chiral 10-heteroazatriquinanes were synthesized from enantiopure asymmetric cis-2,5-disubstituted pyrrolidines through a one-pot tandem cyclization procedure. The structures and configurations of these new chiral 10-heteroazatriquinanes are confirmed by X-ray single-crystal diffraction analysis.
Keywords: cis-2,5-disubstituted pyrrolidine; 10-heteroazatriquinane; tandem cyclization; X-ray single-crystal diffraction analysis